Understanding Collaboration with Virtual Assistants – The Role of Social Identity and the Extended Self - Milad Mirbabaie; Stefan Stieglitz; Felix Brünker; Lennart Hofeditz; Björn Ross; Nicholas R. J. Frick (Business & Information Systems Engineering, 2020)
Organizations introduce virtual assistants (VAs) to support employees with work-related tasks. VAs can increase the success of teamwork and thus become an integral part of the daily work life. However, the effect of VAs on virtual teams remains unclear. While social identity theory describes the identification of employees with team members and the continued existence of a group identity, the concept of the extended self refers to the incorporation of possessions into one's sense of self. This raises the question of which approach applies to VAs as teammates. The article extends the IS literature by examining the impact of VAs on individuals and teams and updates the knowledge on social identity and the extended self by deploying VAs in a collaborative setting. Using a laboratory experiment with N0.167em=0.167em50, two groups were compared in solving a task, where one group was assisted by a VA, while the other was supported by a person. Results highlight that employees who identify VAs as part of their extended self are more likely to identify with team members and vice versa. The two aspects are thus combined into the proposed construct of virtually extended identification explaining the relationships of collaboration with VAs. This study contributes to the understanding on the influence of the extended self and social identity on collaboration with VAs. Practitioners are able to assess how VAs improve collaboration and teamwork in mixed teams in organizations.
Keywords: 000; Virtual collaboration; Virtual assistants; Social identity theory; Extended self; Information systems; Organizations; Virtually extended identification